2008
DOI: 10.1111/j.1440-1746.2007.04988.x
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin for rats with thioacetamide‐induced liver failure and encephalopathy

Abstract: Simvastatin improved encephalopathy and survival in TAA-administered rats. The beneficial effect was offset by L-NAME, suggesting the role of NO in liver damage and encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Then, over longer periods, there is greater deterioration from celecoxib, the COX-2-inhibitor, and the NO synthetase (NOS)-blocker L-NAME when combined, along with prominent rescue by the stable pentadecapeptide BPC 157 and less prominent attenuation with the NOS substrate L-arginine. These findings should likely reveal an aggravating parallelism between COX-2 and NOS inhibition[ 43 ], including the role of the NO system in gastrointestinal[ 2 , 3 ] and liver damage and hepatic encephalopathy[ 4 ] as well as celecoxib syndrome in particular NO system pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, over longer periods, there is greater deterioration from celecoxib, the COX-2-inhibitor, and the NO synthetase (NOS)-blocker L-NAME when combined, along with prominent rescue by the stable pentadecapeptide BPC 157 and less prominent attenuation with the NOS substrate L-arginine. These findings should likely reveal an aggravating parallelism between COX-2 and NOS inhibition[ 43 ], including the role of the NO system in gastrointestinal[ 2 , 3 ] and liver damage and hepatic encephalopathy[ 4 ] as well as celecoxib syndrome in particular NO system pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that celecoxib, a specific COX-2 blocker, causes gastrointestinal, liver and brain lesions in rats when given in high doses, as has already been shown with non-selective nonsteroidal antiinflammatory drugs (NSAIDs)[ 1 ]. These results should also be related to the hitherto undetermined interaction with NO system dysfunction as well presenting the role of the NO system in gastrointestinal lesions[ 2 , 3 ], liver damage and hepatic encephalopathy[ 4 ]. These findings would correspond to hitherto reported lesions after the use of non-selective NSAIDs[ 5 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NO system is important in liver injury and hepatic encephalopathy (Huang et al 2008), as well as in gastrointestinal mucosa maintenance (Sikiric et al 1997b), while diclofenac toxicity has been demonstrated to involve the pathways of the NO system (Evans and Whittle 2001;Seitz and Boelsterli 1998). Also, BPC 157 has been shown to influence the early growth response 1 (egr-1) gene (Tkalcevic et al 2007), which is critical for the development of liver lesions, chronic ethanol-induced steatosis (Donohue 2007), hepatic injury during acute inflammation and/or hepatitis (Pritchard et al 2007), gastrointestinal (cysteamine) ulcers, while NSAIDs delay ulcer healing and hinder angiogenesis by inhibiting egr-1 (Deng et al 2008a,b;Szabó et al 2001).…”
Section: Route Of Medication Medicationmentioning
confidence: 99%
“…Involvement of nitric oxide in the development of HE was investigated in our previous study 35 . Nitric oxide inhibitors deteriorate HE and significantly increased mortality in rats with acute liver failure 36,37 .…”
Section: Discussionmentioning
confidence: 98%